2022
DOI: 10.1038/s41467-022-32103-8
|View full text |Cite
|
Sign up to set email alerts
|

Unified classification and risk-stratification in Acute Myeloid Leukemia

Abstract: Clinical recommendations for Acute Myeloid Leukemia (AML) classification and risk-stratification remain heavily reliant on cytogenetic findings at diagnosis, which are present in <50% of patients. Using comprehensive molecular profiling data from 3,653 patients we characterize and validate 16 molecular classes describing 100% of AML patients. Each class represents diverse biological AML subgroups, and is associated with distinct clinical presentation, likelihood of response to induction chemotherapy, risk o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
115
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(122 citation statements)
references
References 66 publications
7
115
0
Order By: Relevance
“…Recent research demonstrated that ML applied to AML is able to predict new subgroups and prognostic scores [36 ▪ ]. Similarly, Papaemmanuil's work prototyped clinical decision support tools that deliver a personalized risk score based on cytogenetics and the mutational status of 32 genes [37 ▪▪ ].…”
Section: Future Directions In Acute Myeloid Leukamia: Integration Of ...mentioning
confidence: 99%
“…Recent research demonstrated that ML applied to AML is able to predict new subgroups and prognostic scores [36 ▪ ]. Similarly, Papaemmanuil's work prototyped clinical decision support tools that deliver a personalized risk score based on cytogenetics and the mutational status of 32 genes [37 ▪▪ ].…”
Section: Future Directions In Acute Myeloid Leukamia: Integration Of ...mentioning
confidence: 99%
“…17 While some AML subtypes are characterized by recurrent genetic translocations or mutations associated with particular prognoses, most AMLs present a normal or complex karyotype, and identifying key factors that predict treatment resistance in these patients represents a major challenge. [17][18][19][20][21][22] Aside from disease stratification, AML also belongs to malignancies with the lowest mutational burdens, 23 and finding tumor-specific antigens for immunotherapeutic approaches remains very difficult as the frequency of mutations creating neoantigens is expected to be low. 24 In this context, HERV-derived antigens could represent a unique source of alternative tumor-specific antigens (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Acute myeloid leukemia (AML) is a term given to a rare, highly fatal, group of blood cancers 1 . The genetic etiology of AML has been well characterized [2][3][4][5] , and genomic analysis performed at the time of AML diagnostic evaluation can help predict response to therapy [6][7][8] , identify patients eligible for specific molecularly targeted therapies [9][10][11][12] , and stratify patients for risk of subsequent relapse and death in those who achieve an initial complete remission to therapy 3,13,14 .…”
Section: Introductionmentioning
confidence: 99%